Aplication of evidence-based tools for optimization of geriatric pharmacotherapy - Catić Djordjević, Aleksandra (Archives of Pharmacy, 2022)
Progress of pharmacotherapy and ageing in general caused increased prevalence of multimorbidity, polypharmacy and inappropriate prescribing as well in older people. Inappropriate prescribing and use of potentially inappropriate medications (PIM) can be associated with adverse outcomes, hospitalization, even death. Pharmaceutical care includes validated tools for medication review, which have been aimed to objective identification of the prevalence and type of PIMs, potentially prescribing omissions and associated factors as well. Most of the tools focus on pharmacological appropriateness of prescribing - prescribing without clinical indications, omission of needed drugs, incorrect prescription. Screening Tool of Older Person’s Prescriptions/Screening Tool to Alert Doctors to right Treatment (STOPP/START) is one of the most popular tools. Across several European countries nowadays we have European Potentially Inappropriate Medication - EU (7) PIM and International Consensus of a Clinical Tool for Improved Drug Treatment in Older People (FORTA) and others national PIM list. In conducted study, with 880 enrolled patients at least one STOPP or START observed in 49-74.2% and 39.5-53.3% patients, retrospectively. The most common STOPP criteria were: drug indication (35.6%), fall-risk drugs (32.3%) and central nervous system drugs (28.3%). More than 30% of all patients showed underprescription of drugs affecting cardiovascular system. Age and number of drugs were significantly associated with the occurrence of STOPP and START criteria. In addition to the technological challenge, the integration of explicit criteria into the prescribing and dispensing system, especially electronic, is an overall geriatric pharmacotherapy concept that regularly re-evaluates chosen drugs and optimizes dose regimens.